2021
DOI: 10.1038/s42005-020-00511-1
|View full text |Cite
|
Sign up to set email alerts
|

Varying pre-plasma properties to boost terahertz wave generation in liquids

Abstract: Laser-driven nonlinear phenomena can both reveal the structural features of materials and become the basis for the development of various translated technologies, including highly intense terahertz sources. Here we realize a modified single-color double-pulse excitation scheme for enhancing the terahertz wave generation in flat liquid jets, and we show that the pre-ionization effect is crucial for finding the optimal input conditions. The experimental results, being supported by numerical simulations, reveal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 23 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…Figure 2(b) demonstrates spectrum modulus of such THz pulse as well as the normalized modulus of changes in this spectrum due to quadratic and cubic nonlinearity of the medium (11,12) in the THz frequency range. Figure 2(c) demonstrates the spectrum modulus of the THz pulse after its propagation in nonlinear medium (9). The maximum of the spectrum modulus corresponds to the frequency of ν max equals to 1 THz (τ = 10 It can be seen from Fig.…”
Section: Analytical Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 2(b) demonstrates spectrum modulus of such THz pulse as well as the normalized modulus of changes in this spectrum due to quadratic and cubic nonlinearity of the medium (11,12) in the THz frequency range. Figure 2(c) demonstrates the spectrum modulus of the THz pulse after its propagation in nonlinear medium (9). The maximum of the spectrum modulus corresponds to the frequency of ν max equals to 1 THz (τ = 10 It can be seen from Fig.…”
Section: Analytical Resultsmentioning
confidence: 92%
“…The very first source of electromagnetic THz radiation was created at the beginning of the last century by the Soviet scientist A.A. Glagoleva-Arkadyeva 5 . In recent years methods have been developed for efficient generation of high-intensity pulsed THz radiation, for example, the method of optical rectification 6 or generation in plasma [7][8][9] . Under the excitation of high-intensity THz radiation, nonlinear effects of media begin to play a significant role [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Anand et al reported a 68-times increase in the intensity of hard X-ray emission from methanol droplets irradiated by double-pulsed femtosecond laser pulses with a delay time of 10 ns [75]. Doublepump excitation is also studied in THz wave generation [16,[76][77][78][79]. Recently, THz generation enhancement by several orders of magnitude in power is observed from gallium droplets under double pump excitation [80].…”
Section: Thz Wave Enhancement Under Double-pump Optical Excitationmentioning
confidence: 99%
“…Usually, pulsed THz radiation has low energies 29 , 30 , but there are already widespread methods of generating high-energy radiation, for example, such as in organic crystals 31 , 32 or by filamentation in gases or liquids 33 , 34 . The generation of speckle structures by pulsed THz radiation has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%